Carbapenem-resistant Klebsiella pneumoniae outbreak in a COVID-19 intensive care unit; a case-control study. (17th November 2022) - Ergen, Pınar; Koçoğlu, M. Esra; Nural, Müge; Kuşkucu, Mert Ahmet; Aydin, Özlem; İnal, Ferda Y. and Öztürk, Hande and Üçişik, Ayşe C. and Çaşkurlu, Hülya and Güneysu, Büşra and Yildirim, Büşra and Midilli, Kenan and Çağ, Yasemin and Arslan, Ferhat and Vahaboglu, Haluk
Abstract: We analysed a carbapenem-resistant Klebsiella pneumoniae (CRKP) outbreak in the coronavirus disease (COVID) ICU. We retrospectively collected data from ICU records. We identified 25 cases between 12 November 2020 and 19 December 2020, and compared them to 42 controls present in the ICU during the same period. The presence of a femoral haemodialysis catheter was strongly associated with invasive CRKP infections (cases, 9 [36%]; controls, 0 [0%]; odds ratio [OR] 95% confidence intervals [CIs], 21 (5; 89)). We found a significant association between old age and CRKP infection with adverse outcomes. Sequence analysis revealed three distinct carbapenemase genes: bla NDM-1, bla OXA-48 and bla KPC-2 . We launched rectal swab sampling upon admission to the ICU, cohorted colonized patients and cases and conducted an intensive training programme for newly employed staff. This study revealed that the emergence and dissemination of CRKP in COVID ICUs were associated with increased adverse outcomes. The presence of a femoral haemodialysis catheter was a significant risk factor for CRKP infections.